Characterising admissions to Mental Health beds in general hospitals - Schinemann, Vanderl´éia; Zambenedetti, Gustavo (Argumentum, 2020)
In the context of psychiatric reform there are proposals for reconfiguring the location and model of care, to move beyond hospitalisation. But there is resistance to their implementation, making hospitalisation an important subject for analysis and reflection. This article aims to characterise admissions to Mental Health Beds in General Hospitals in the interior of Paraná from September 2014 to December 2017. It is an analysis based on qualitative descriptive research using the Institutional Analysis theoretical-methodological approach. We highlight some strengths of this service, such as the fact that it is regionalised, and has an average hospital stay of less than 7 days with low numbers of readmissions and transfers to other services.